2015
DOI: 10.18869/acadpub.irjns.1.2.40
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surgical Treatment in Traumatic Subdural Hygroma: A Pilot Study

Abstract: Background and Aim: Traumatic subdural hygroma is the accumulation of CSF (cerebrospinal fluid) in subdural space following head trauma. The mass effect of hygroma on brain can impinge on consciousness. There are still many ambiguities on indications of hygroma surgery. This is an 11-year follow-up study which involves the patients suffering traumatic subdural hygroma who underwent surgery. Methods & Materials/Patients: In this retrospective study, clinical records of 16 patients who were operated due to traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…They were 2/5 patients (40%) in the conservative group and 2/2 patients (100%) in the surgical group. Many authors reported similar results with a high percentage of good outcome in the younger groups of patients [11] [21]. Severity of brain injury at time of admission is the main factor in determining clinical outcome of the patients regardless of the type of management, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…They were 2/5 patients (40%) in the conservative group and 2/2 patients (100%) in the surgical group. Many authors reported similar results with a high percentage of good outcome in the younger groups of patients [11] [21]. Severity of brain injury at time of admission is the main factor in determining clinical outcome of the patients regardless of the type of management, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 72%
“…Whereas patients with mild and moderate GCS showed good recovery (19/22 patients, 86%) regardless of type of management they had (Table 4). Many authors reported similar results with a high percentage of good outcome in patients with mild and moderate Glasgow Coma Score [11] [21] [24]. Other factors as age, gender, site of SDHy or associated pathology had not yet reached a statistical significant value in determining the clinical outcome or even the type of management of patients with subdural hygroma.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Reducing the causes of dissatisfaction and correcting them can reduce the burden of clients' dissatisfaction [21][22][23][24]. Also, dissatisfaction can be greatly reduced by informing the clients about the course of the treatment process [25].…”
Section: Discussionmentioning
confidence: 99%